The Role and Importance of Hr in Talent Management (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article gives information about the crucial role that human resources (HR) play in talent management and it makes the case that HR is in charge of finding, nurturing, and keeping top talent within an organization. HR also plays a key role in developing a talent strategy that is in line with the overarching business objectives of the organization. Practical tips and strategies for HR professionals to effectively manage talent, including conducting regular performance evaluations, providing ongoing training and development opportunities, and creating a positive work environment are explained in the article.